The impact of bedside handovers on relevant clinical indicators: A matched‐controlled multicentre longitudinal study. (25th May 2020) - Malfait, Simon; Eeckloo, Kristof; Van Opdorp, Lara; Van Biesen, Wim; Van Hecke, Ann
Abstract: Aim: To investigate the effects of bedside handover, as contrasted with traditional handovers, on length of hospital stay, unplanned readmission, hospital‐acquired pressure ulcers (HAPUs), patient falls, unscheduled intravenous reinfusion and pain. Design: A multicentre matched‐controlled longitudinal design. Method: Bedside handover was implemented at five intervention wards in a convenience sample of four hospitals (three surgical/medical wards and two wards for medical rehabilitation). Four control wards continued to use their traditional handover (two surgical‐medical wards, one medical rehabilitation ward and one mixed surgical‐medical rehabilitation ward; one for each hospital). Patient records, including reports on individual patients in the electronic incident reporting systems, were consulted ( N intervention = 509; N control = 265). The study was carried out between May 2016–February 2018 and data were collected between March 2018–June 2018. The data were analysed using generalized linear mixed‐model analysis. Results: No significant differences in length of stay, unplanned readmission, HAPUs, unnecessary intravenous drips, pain or patients falls could be attributed to the use of bedside handovers, whether over time or between the intervention and the control groups. Conclusion: No long‐term effects were found on patient safety arising from bedside handover. This lack of significance possibly indicates that: (a) caution is needed when generalizing the results of previous smaller‐scale studies; and that (b) bedside handovers do not create hazardous situations for patients. Impact: Nurses traditionally perform change‐of‐shift handovers without the patient. However, the growth in attention paid to reducing adverse events and the demand for more participative and patient‐centred approaches in health care both suggest that bedside handovers might be a logical intervention. This study could not confirm the positive results found in the international literature on the impact of bedside handovers on patient safety. Bedside handover should thus be considered as an equally safe, more patient‐centred alternative to traditional handover models. Trial registration: ClinicalTrials.gov (NCT02714582). Abstract : 目的: 本研究旨在探讨与传统交接班比较, 床边交接班对住院时间、非计划再入院、医院获得性压疮(HAPU)、患者跌倒、非计划性静脉再注射和疼痛的影响。 设计: 一项多中心匹配对照纵向设计。 方法: 在4家医院(3个外科/内科病房和2个医疗康复病房)的便利样本中, 对5个干预病房实施了床边交接班。4个对照病房继续采用传统的交接班方式(2个内外科病房、1个医疗康复病房和1个外科‐医疗康复综合病房;每家医院一个)。查阅了病历, 包括电子事件报告系统中关于个别患者的报告(N干预组=509;N对照组=265)。研究时间为2016年5月至2018年2月, 数据收集时间为2018年3月至2018年6月。采用广义线性混合模型分析法对数据进行分析。 结果: 无论是随着时间的推移还是在干预组和对照组之间, 在住院时间、非计划再入院、医院获得性压疮(HAPU)、非必要的静脉滴注、疼痛或患者跌倒等方面均无显著差异, 这可归因于床边交接班的应用。 结论: 未发现床边交接班对患者的安全产生长期影响。这种缺乏意义的情况可能表明:(a)在对以往较小规模的研究结果进行汇总时, 需保持谨慎态度;(b)床边交接班不会使患者陷入危险情况。 影响: 传统上, 护士是在没有患者参与的情况下进行换班交班的。然而, 越来越多的人关注减少不良事件的发生, 并且对更多地参与医疗保健和以患者为本的医疗方法的需求逐渐增加, 这些均表明, 床边交接班可能是一种合理的干预措施。本研究无法证实国际文献中关于床边交接班对患者安全起着正面影响的结论。因此, 应将床边交接班视为是一种与传统交接班模式同样安全、更以患者为本的替代方法。 试验注册: ClinicalTrials.gov(NCT02714582)。